The patent foramen ovale may alter migraine brain activity: A pilot study of electroencephalography spectrum and functional connectivity analysis - Lei, Xiangyu; Wei, Meng; Qi, Yi; Wang, Liang; Liu, Chenyu; Guo, Yichen; Xu, Yue; Cao, Xiangqi; Liu, Rui; Luo, Guogang (Frontiers in Molecular Neuroscience, 2023)
Background A link has been shown between patent foramen ovale (PFO) and migraine, particularly migraine with aura. However, it is unknown if PFO might cause migraine by altering cortical excitability and neural network, which may lower the threshold of cortical spreading depression (CSD). This study aims to compare the spectrum power and functional connectivity of the alpha and beta bands of electroencephalography (EEG) across migraine patients with and without PFO. Methods Thirty-five migraine patients with PFO (PFO +), 35 migraine patients without PFO (PFO –) and 20 PFO patients without migraine (control) were enrolled in this cross-sectional analysis. 19-channel EEG was recorded for all patients under resting state and intermittent photic stimulation. Power spectrum density (PSD) and phase lag index (PLI) of alpha and beta bands were then calculated and compared between the three groups. Results During photic stimulation, the beta band PSD at the occipital area was substantially higher in PFO + migraine patients compared to PFO-migraine patients (p < 0.05, Bonferroni corrected). Subgroup analysis showed that both migraine with and without aura patients with PFO had increased PSD in the alpha and beta bands at the occipital region during photic stimulation (p < 0.05, Bonferroni corrected). Meanwhile, the beta band PLI during photic stimulation was significantly elevated (adjusted p = 0.008, utilizing the network-based statistic technique) in PFO + group compared to PFO-group. Furthermore, although failed to pass the correction, the beta band power in the occipital area during photic stimulation at 20 Hz on O1 (R = 0.392, p = 0.024) and O2 channel (R = 0.348, p = 0.047) was prone to positively correlated with MIDAS score, and during photic stimulation at 12 Hz on O2 channel (R = 0.396, p = 0.022) and 20 Hz (R = 0.365, p = 0.037) on O1 channel was prone to positively correlated to HIT-6 score in PFO+ migraineurs, whereas no similar correlation was found in the PFO-group patients. Conclusion The outcomes of this investigation suggested that PFO may change the cortical excitability in the occipital lobe of both migraineurs with and without aura. Meanwhile, the beta band PSD on the occipital area during photic stimulation might be an objective measure of severity in migraineurs with PFO.